2016 IEEE 12th International Conference on Intelligent Computer Communication and Processing (ICCP) 2016
DOI: 10.1109/iccp.2016.7737121
|View full text |Cite
|
Sign up to set email alerts
|

A survey of Ambient Assisted Living systems: Challenges and opportunities

Abstract: The tremendous applications of human activity recognition are surging its span from health monitoring systems to virtual reality applications. Thus, the automatic recognition of daily life activities has become signi cant for numerous applications. In recent years, many datasets have been proposed to train the machine learning models for e cient monitoring and recognition of human daily living activities. However, the performance of machine learning models in activity recognition is crucially affected when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…In this paper an eye-and gaze-tracking mechanism has been presented. Said mechanism enables the user (1) to engage (i.e., open, shut, slide, turn-on/-off, etc.) with a variety of actuable objects and systems deployed within an intelligent built-environment via sight-enabled identification, selection, and confirmation; and (2) to extract and display personal identity information from recognized familiar faces viewed by the user.…”
Section: The User's Attention Is Turned To the Wall-artmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper an eye-and gaze-tracking mechanism has been presented. Said mechanism enables the user (1) to engage (i.e., open, shut, slide, turn-on/-off, etc.) with a variety of actuable objects and systems deployed within an intelligent built-environment via sight-enabled identification, selection, and confirmation; and (2) to extract and display personal identity information from recognized familiar faces viewed by the user.…”
Section: The User's Attention Is Turned To the Wall-artmentioning
confidence: 99%
“…The eye-and gaze-tracking mechanism detailed in this paper is situated within the Active and Assisted Living / Ambient Assisted Living (AAL) discourse [1][2][3][4]. Its objective is to enable the user (1) to open, shut, slide actuable windows and doors as well as to turn lights on or off within an intelligent built-environment via sightenabled identification, selection, and execution; and (2) to extract and display personal identity information from recognized familiar faces viewed by the user.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When conducting this study, we observed that other literature reviews are constrained to some of the dimensions of transferring learning. For example, they may exclusively elaborate about the pose-base of the sensing devices worn [9], the subject's pattern behaviour [12], or specific technology domain like environmental sensing [18,31]. Other papers may discuss the trend classification techniques [17,25].…”
Section: Introductionmentioning
confidence: 99%
“…Technological advancements allow for a preliminary diagnosis through machines without any intervention from healthcare professionals. This research is included in the development of systems to support ambient assisted living technologies [3][4][5][6]. Cutting-edge approaches in the healthcare area have helped in solving various computer vision-based tasks by analyzing different features from various biosignals, including the facial features [7,8].…”
Section: Introductionmentioning
confidence: 99%